Enhancing Home Education in Italian Context: Teachers' Perception of a Hybrid Inclusive Classroom - Vincenza Benigno; Giovanni Paolo Caruso; Francesca Maria Dagnino; Edoardo Dalla Mutta; Chiara Fante (MDPI AG, 2022)
Homebound Education in Italy is based on one-to-one teaching conducted by teachers who visit the sick student at home. This modality does not include interactions between homebound students and classmates, thus inhibiting the educational aspect of peer relationships. With the outbreak of the COVID-19 pandemic and the consequent dispositions of the Ministry of Education regarding remote education and integrated digital didactic (DID), new opportunities became available for homebound students. In this research, we applied and tested in the context of homebound education a model of hybrid inclusive classroom developed in a previous project ((TRIS), addressing homebound students that could not permanently attend school and followed lessons remotely. The present study involved two homebound students affected by chronic and acute diseases. During the 2020/21 school year, the model was proposed to the two school councils (22 teachers in all) and the trial monitored; at the end of the school year, semi-structured interviews were conducted with teachers and transcriptions analyzed using a deductive approach based on the model. Results confirm some findings of the TRIS project, while new aspects emerged linked to the specific context. Overall, the implemented hybrid classroom seems to have positively affected both the learnings and students' inclusion.